A Legal Review of the Rights and Identity of Adopted Children (Case Study of an Adopt Father Who is Reluctant to Disclose Their Biological Father in Sumber Gede Village, East Lampung) - Ariyanto, Ade Fajar; Khotamin, Nur Alfi (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
This study critically examines the practice of concealing the identity of adopted children in kinship-based adoption patterns in Sumber Gede Village, highlighting the implementation of adoption that takes place without formal legal procedures and its implications for the fulfillment of identity rights in the national legal system. This study aims to identify the configuration of these social practices and test their compliance with the provisions on child identity protection in Law Number 35 of 2014 and Government Regulation Number 54 of 2007. The approach used is qualitative through empirical juridical methods based on field studies, with primary data from interviews with various parties and secondary data from regulations and legal literature, which are analyzed qualitatively descriptively. The findings indicate two dominant patterns, namely foster care without document changes and administrative engineering without a court order, which have the potential to reduce children's identity rights. The novelty lies in the integration of normative and empirical-sociological analyses that highlight the psychological-cultural motives of adoptive parents and their legal vulnerabilities. The socio-legal approach reveals the gap between norms and practices, both from the perspective of national law and the principle of ḥifẓ al-nasl, with implications for the uncertainty of civil status and weak legal protection of children.